Peasant Renaissance in Ukraine at the Beginning of the 20th Century: Dmytro Dontsov’s Vision - Kornovenko, Serhii; Morozov, Anatolii (Ukrainian Peasant, 2024)
The goal of the study is to reveal the content of Dmytro Dontsov’s concept of the peasant renaissance, the agrarian component in his theoretical heritage, presented in the work “The Foundations of our Politics”. Conclusions. The WWI and the peasant revolutions in Europe led to the emergence of a new player on the forefront of European history in the early twentieth century - the peasantry. According to D. Dontsov, “from a disheveled white slave, a slave of the city,” the peasant became the center, “the axis around which the entire economic life of the countries torn by war begins to revolve.” In fact, the emergence of this peasant-centeredness is the peasant renaissance in Central and Southeastern Europe in general and in Ukraine in particular. The revival of the peasantry, according to the philosopher’s concept, led to its priority in the following areas: 1) economy; 2) defense. In the Ukrainian realities of that time, the thinker believed that “cradle of the nation... has now released weapons from its weak hands.” In view of this, he believed that it was logical to turn to the peasantry and political influence. Factually, Dontsov argues in favor of the peasantry as the leader of the modern Ukrainian nation, the peasantry as the bearer of Ukrainian identity, the embodiment of national ideals and virtues, and the socioeconomic and socio-political basis of Ukrainian statehood. He recognized without humiliation that Ukrainians are a peasant nation. “The Ukrainian peasant has already made his revolution and no longer needs any other,” the philosopher stated. In Dontsov’s concept of the peasant renaissance, we can observe the intelligent and critical peasant-centeredness of its author. The thinker realized that in the early twentieth century the peasantry was not fully prepared for state-building. At the same time, in the context of the Ukrainian Revolution of 1917-1921, the peasantry acted, to use modern terminology, as a trigger for the then nonlinear processes of Ukrainian nation-building